Family [videorecording (DVD)] - Steinel, Laura; Schilling, Taylor, 1984-; Henry, Brian Tyree; Vale, Bryn; McKinnon, Kate, 1984- (Universal Pictures Home Entertainment, 2019)
It tells the story of eleven-year-old Maddie, a social misfit who practices karate moves with trees. Her self-absorbed, childless aunt, Kate, offers to take care of her for a week while Maddie's parents are busy, and it proves to be the most transformative week of young Maddie's life.